The Role Of Judicial Review In Protecting Religious Minority Rights In Indonesia - Maula, Bani Syarif (Veteran Law Review, 2018)
Indonesia is a predominantly Muslim country, and Muslims in this country live in a pluralistic society harmoniously in their daily life. The absence of any reference to Islam in the Constitution shows that Indonesia is open to all religions besides Islam. The harmony of relationship among religious followers is preserved in the Indonesian constitution that acknowledges all of citizens have the religious freedom, which the state has to respect, protect and fulfill. The general idea of preserving the rights of religious freedom lies in the history of protecting religious minorities, and it is universally acceptable as one of the foundations of a democratic society. Therefore, ideally, a law which limits civil rights should never threaten the freedom of thought, conscience and religion, or impose limitations to those rights solely on the grounds of religious, political or other views. If the notion of protecting rights is as such, then the question arises is what mechanism can protect human rights as constitutional rights of citizens? The best legal mechanism in this context is to challenge the state and constitutional issues through the courts by means of the judicial review. This paper examines whether the judicial review as one of the best mechanisms to protect constitutional rights of citizens can be a concrete way to deal with human rights protection by challenging the state through the court. This paper concludes that the judicial review of executive acts and legislative power is very likely to be able to protect religious minority rights in Indonesia.